Factors affecting patient valuations of caries prevention: Using and validating the willingness to pay method. Issue 8 (August 2015) - Vernazza, Christopher R.; Wildman, John R.; Steele, Jimmy G.; Whitworth, John M.; Walls, Angus W.G.; Perry, Ross; Matthews, Roger; Hahn, Petra; Donaldson, Cam
Abstract Objectives Determining the value of, or strength of preference for health care interventions is useful for policy makers in planning health care services. Willingness to pay (WTP) is an established economic technique to determine the strength of preferences for interventions by eliciting monetary valuations from individuals in hypothetical situations. The objective of this study was to elicit WTP values for a dental preventive intervention and to analyze the factors affecting these as well as investigating the validity of the WTP method. Methods Patients aged 40 years plus attending dental practices in the UK and Germany were recruited on a consecutive basis over one month. Participants received information about a novel root caries prevention intervention. They then completed a questionnaire including a WTP task. Where the coating was indicated, patients were offered this for a payment and acceptance was recorded. Analysis included econometric modelling and comparison of expected (based on stated WTP) versus actual behaviour. Results The mean WTP for the coating was £96.41 (standard deviation 60.61). Econometric models showed that no demographic or dental history factors were significant predictors of WTP. 63% of the sample behaved as expected when using stated WTP to predict whether they would buy the coating. The remainder were split almost equally between those expected to pay but who did not and those who were expected to refuse but paid. Conclusions Values for a caries preventive intervention had a large and unpredictable variance. In comparing hypothetical versus real preferences both under- and over-valuation occurs. Clinical significance Wide and unpredictable variation in valuations for prevention may mean that there are difficult policy questions around what resource should be allocated to dental prevention and how to target this resource.